(untitled) (Bangladesh Journal of Public Administration, 2022)
The lack of good seeds is one of the significant obstacles to Grain Production. This study intends to investigate the circumstances surrounding the availability of quality seeds for rice cultivation and establish policy strategies for quality seed production at the farmer level. The study focused on rice and a significant grain crop, and data were gathered using several survey questionnaires and in-person interviews. The acquired data was gathered and reviewed to write a paper utilizing the quantitative technique. The findings showed that farmers utilize between 70 and 80 percent of their rice seed throughout the research regions. Farmers (20–30%) can acquire rice seeds from NGOs, seed dealers, Bangladesh Agricultural Development Corporation (BADC), the Department of Agricultural Extension (DAE), and other external sources in the most extensive quantities. However, practically all farmers rely entirely on seed dealers or companies for their hybrid rice seeds. Keywords: ; Rice; Food Security; Yield.